Influence of Sustainable Leadership, Social Factors and Technological Infrastructure on MSME Business Sustainability in the Modern Era - Judijanto, Loso; Arisanti, Ivon; Papia, Jedithjah Naapia Tamedi; Abidin, Zainal (International Journal of Business, Law, and Education, 2024)
This research explores the influence of sustainable leadership, social factors, and technological infrastructure on the sustainability of Micro, Small, and Medium-sized Enterprises (MSMEs) in the modern era. The study employs a mixed-methods approach, combining qualitative and quantitative methods. The sample includes MSMEs from various industries, and data is collected through surveys, interviews, and archival sources. The analysis involves Partial Least Squares Structural Equation Modeling (PLS-SEM) for quantitative data and systematic interpretation for qualitative data. The results indicate a positive and significant relationship between sustainable leadership, social factors, technological infrastructure, and business sustainability. Sustainable leadership is found to enhance organizational resilience and performance. Social factors, including community engagement and corporate social responsibility, contribute to brand loyalty and long-term viability. Technological infrastructure, encompassing advanced technologies, improves operational efficiency and fosters innovation. The study has implications for leadership development, stakeholder engagement, technological adoption, and policy considerations. Limitations include contextual specificity and the need for refined measurement instruments. Future research could explore different industries, longitudinal trends, and causal relationships.